Tradução, adaptação cultural e validação da RIS Eldercare Self-Efficacy Scale (Escala de Autoeficácia do Cuidador de Pessoas Idosas) - Alves, Ludmyla Caroline de Souza (2024)
Caregiver self-efficacy can be understood as the ability they believe they have to perform a task. Instruments that assess this domain can help in the construction of interventions capable of positively impacting the care process. Therefore, the translation and adaptation of instruments such as the RIS Eldercare Self-Efficacy Scale is important for the Brazilian context. Objective: Translate, culturally adapt and validate the RIS Eldercare Self-Efficacy Scale for the Brazilian context in informal caregivers of people living with dementia. Method: Study of the methodological type for translation and cultural adaptation of the instrument entitled RIS Eldercare Self-Efficacy Scale for the Brazilian context, for informal caregivers of people living with dementia. The translation process was carried out by qualified translators, following the steps recommended in the literature. For cultural adaptation, a committee of experts was formed, who analyzed the data in a descriptive way, and the validity of the content through the Content Validity Index. For validation, people aged 18 or over, literate and who were informal caregivers of a person living with dementia participated online. Data on sociodemographic characterization, self-efficacy (RIS Eldercare Self-Efficacy Scale), overload (Zarit Overload Inventory), and anxious and depressive symptoms (Hospital Anxiety and Depression Scale) were collected from 100 participants. All ethical precepts were respected. For data analysis, Confirmatory Factor Analysis (CFA) was carried out to verify the structure of the Brazilian version of the RIS Eldercare Self-Efficacy Scale, adopting the same evaluation criteria as the original version of the scale. After the CFA, Spearman Correlation tests were performed and internal consistency was assessed using Cronbach's alpha coefficient. For statistical tests, a significance level of 5% was adopted (p value ≤ 0.05). Results: After translation and back-translation, word adaptations were necessary for better understanding by caregivers, as well as adjustments in the writing of answer options, authorized by the author of the original version. Content and semantic validation were achieved. The content validity coefficient was greater than 0.80. Final considerations: After the established methodological steps, the scale was adapted to Brazilian culture, presenting conceptual, semantic and cultural equivalence, compared to the original version. Therefore, the scale can be used to assess the self-efficacy of informal caregivers of elderly people living with dementia.